Critical Discourse Analysis on Banyumas Tourism Promotion Media - Eka Dyah Puspita Sari; Indah Puspitasari; Gigih Ariastuti Purwandari; Kristianto Setiawan (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2024)
High occupancy in Banyumas tourism sector is fruitful for society. To gain it, support from various parties is needed. One of the ways is by promoting tourism spots. This study aims to analyze the grammatical pattern, the relationship pattern, and the social phenomena in promotion media. It applied literature review and field study by implementing descriptive qualitative method to get the data. They were taken from four tourism spots. They were analyzed and divided into three structures of critical discourse analysis. The analysis showed some results. The first result showed that the diction and the sentence structure of printed and online media were different. The second analysis showed that production, consumption, and distribution of printed and online media were quite different. It could be clearly seen in the absence of various different elements on both of them. The last result showed that both printed and online media held the main function as information media, but the situational, institutional, and social aspects were different. It can be concluded that conducting critical discourse analysis is beneficial when it comes to promote tourism because it can give clear views for the tourism providers to make their promotion better.